Sleep Related Epilepsy and Pharmacotherapy: An Insight - Kumar, Jaya; Solaiman, Amro; Mahakkanukrauh, Pasuk; Mohamed, Rashidi; Das, Srijit (Frontiers in Pharmacology, 2018)
In the last several decades, sleep-related epilepsy has drawn considerable attention among epileptologists and neuroscientists in the interest of new paradigms of the disease etiology, pathogenesis and management. Sleep-related epilepsy are nocturnal seizures that manifest solely during the sleep state. Sleep comprises two distinct stages i.e. non-rapid eye movement (NREM) and rapid eye movement (REM) that alternate every 90 mins with NREM preceding REM. Current findings indicate that the sleep-related epilepsy manifests predominantly during the synchronized stages of sleep; NREM over REM stage. Nocturnal frontal lobe epilepsy (NFLE), benign partial epilepsy with centrotemporal spikes or benign rolandic epilepsy (BECTS), and Panayiotopoulos Syndrome (PS) are three of the most frequently implicated epilepsies occurring during the sleep state. Although some familial types are described, others are seemingly sporadic occurrences. In the present review, we aim to discuss the predominance of sleep-related epilepsy during NREM, established familial links to the pathogenesis of NFLE, BECTS and PS, and highlight the present available pharmacotherapy options.